Influence of Personality-Traits and Learning Styles on Distance Learners’ Academic Performance in University of Cape Coast - John Ekow Laryea (Universitas Mathla'ul Anwar Banten, 2018)
The aims of the study was to investigate the influence of personality-traits and learning styles on academic performance of University of Cape Coast (UCC) distance learners, taking into consideration the moderating effects of academic self-discipline and academic self-confidence. The correlational research design was adopted. The sample was 805, made up of 10 centre coordinators, 763 level 200 Diploma in Basic Education (DBE) students and 32 course tutors. The stratified sampling procedure that makes use of the random number method of simple random sampling technique was used to select all the respondents. Questionnaire and interview-guide were the instruments used. The quantitative data was analysed using both descriptive and inferential statistics, while the qualitative data were analysed manually using the thematic approach. The study revealed that openness to experience traits that students demonstrate contributes more to their likelihood of obtaining high level academic performance. Also, students prefer using read/write and visual learning styles. Furthermore, students’ personality-traits and learning styles have significant influence on students’ academic performance. However, this influence becomes stronger indirectly through the moderating effect of students’ academic self-discipline and self-confidence.